Gifts from Nature: Bio‐Inspired Materials for Rechargeable Secondary Batteries. Issue 37 (1st August 2021) - Jo, Chang‐Heum; Voronina, Natalia; Sun, Yang‐Kook; Myung, Seung‐Taek
Abstract: Materials in nature have evolved to the most efficient forms and have adapted to various environmental conditions over tens of thousands of years. Because of their versatile functionalities and environmental friendliness, numerous attempts have been made to use bio‐inspired materials for industrial applications, establishing the importance of biomimetics. Biomimetics have become pivotal to the search for technological breakthroughs in the area of rechargeable secondary batteries. Here, the characteristics of bio‐inspired materials that are useful for secondary batteries as well as their benefits for application as the main components of batteries (e.g., electrodes, separators, and binders) are discussed. The use of bio‐inspired materials for the synthesis of nanomaterials with complex structures, low‐cost electrode materials prepared from biomass, and biomolecular organic electrodes for lithium‐ion batteries are also introduced. In addition, nature‐derived separators and binders are discussed, including their effects on enhancing battery performance and safety. Recent developments toward next‐generation secondary batteries including sodium‐ion batteries, zinc‐ion batteries, and flexible batteries are also mentioned to understand the feasibility of using bio‐inspired materials in these new battery systems. Finally, current research trends are covered and future directions are proposed to provide important insights into scientific and practical issues in the development of biomimetics technologies for secondary batteries. Abstract : Bio‐inspired materials have technical advantages in application as major components of secondary batteries as well as environmental and economic advantages. The recent research progress on utilization of biomaterials for electrodes, separators, and binders for the improvement of the performance of rechargeable batteries is highlighted and summarized. Current challenges and perspectives regarding the use of biomaterials for secondary batteries are given.